Les élections françaises de 1981 et la politique étrangères - Ménudier, Henri (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
In the two electoral campaigns held in France in the spring of 1981, parties and their candidates gave only limited importance to foreign policy. They showed some interest during the presidential campaign but very little during the legislative elections. This relative silence can be explained by the fact that the French are in rather wide-spread agreement as to the over-all orientation of foreign policy as defined in the 1960s by General de Gaulle and as adapted subsequently by his successors. Clearly, economic and social questions dominated the electoral discussions.Valery Giscard d'Estaing defended his seven-year record; his opponents in the outgoing majority and on the left sharply contested it. Without abandoning a critical position, François Mitterand tried to reassure the French by showing them that his coming to power would not upset the foundations of foreign policy and that changes would be more important in other areas. A thematic study of arguments used during the electoral campaign shows that Valery Giscard d'Estaing's opponents forcefully reproached his overall conception of foreign policy defined by "globalism" and his attitute toward the USSR following the invasion of Afghanistan. The meeting between the French president and Leonid Brejnev in Warsaw was at the heart of the polemic. Even if weak arguments were used in other areas of foreign policy, international problems did in the end play a significant role in challenging the credibility of the outgoing president. Foreign policy became a tool used for electoral purposes. The electoral campaign was characterized as well by the involvement of pressure groups, notably Jewish organizations discontent with French policy toward the Middle East and by the active support of the Socialist International in favor of François Mitterand. On the whole, the electoral campaign emphasized continuity more than change. It is useful to be aware of these positions in order to understand France s foreign activities under its socialist regime.